Factors affecting graduate employability among Management & Science University (MSU) undergraduates student in Sungai Petani, Kedah and Georgetown, Pulau Pinang / Mohamad Nazmi Mohamad Adzhar and Mohd Asyraf Sarudin - Mohamad Adzhar, Mohamad Nazmi; Sarudin, Mohd Asyraf (2019)
McQuaid and Linda (2005) expressed that employability was an unclear idea in the previous decade in various studies it revealed that employability assumes a significant job in deciding the United Kingdom work showcase approach, in some European nations and different nations .however, Lim (2008) characterizes employability as graduate’s labor market results and number of days jobless or likelihood of jobless furthermore, Lim expressed that on average the graduates are encountering a sum of 138 days of being jobless which is likeness 4.6 months. Nevertheless, this study conceptualizes employability as the capacity of the higher learning institute student to be utilized or to act naturally utilized towards the industries. According to Yorke (2003) employability skills can be define as a set of achievements, skills, understandings and personal attributes that make graduates more likely to gain employment and be successful in their chosen occupations, which benefits themselves, the workforce, the community and the economy in Malaysia Graduate employability is a rising concern as graduates represent a whopping 23 per cent of total youth unemployment in the country according to Bank Negara Malaysia (2017). The study by Rahmah et al. (2011), it have been reported One of the factor that contribute to the unemployment of the fresh graduates is graduates are lack of employability skill Meanwhile, With the reference of graduate employability survey conducted by ministry of higher education in 2016, a private university graduate’s employability number are lower than public university in the last few years due to the private university student are tend to be lack of confident and bit assertive. Therefore this paper represent a review of graduate employability among MSU undergraduates student in Sungai Petani, Kedah and Georgetown Pulau Pinang,